Exploring disparities in receipt of adjuvant chemotherapy in culturally and linguistically diverse groups: an Australian centre's experience. Issue 5 (2nd May 2018) - Thai, Alesha A.; Tacey, Mark; Byrne, Amanda; White, Shane; Yoong, Jaclyn
Abstract: Background: Globally, racial and ethnic disparities exist in treatments and outcomes for cancer patients. In Australia, there are few published data related to cancer patients from culturally and linguistically diverse (CALD) backgrounds. Aim: To explore disparities in adjuvant chemotherapy utilisation in cancer patients from CALD groups. Methods: Retrospective analysis of patients who were recommended adjuvant chemotherapy for early stage breast cancer or early stage colorectal cancer between July 2011 and October 2014 was performed. Rates of adjuvant chemotherapy uptake were analysed between those who identified English as their first‐preferred language, versus those who did not, as well as between patients who were born in a country where English is the main language (non‐CALD), versus those born in a country where English is not the main language (CALD). Results: Two hundred and eleven patients were identified. One hundred and forty‐three (67.7%) patients had early stage breast cancer and 68 (32.2%) patients had early stage colorectal cancer. No difference was detected in the acceptance of adjuvant chemotherapy between non‐CALD (80.9%) and CALD patients (81.3%, P = 0.984) or between patients who identified English as their first‐preferred language (80.8%) and those who did not (81.8%, P = 0.870). There was no difference in the rate of chemotherapy completion, with 75.6% completion in the non‐English‐speaking group and 81.1% in the English‐speaking group ( P = 0.426). Conclusion: No difference was observed in adjuvant chemotherapy utilisation in patients who identified English as their first‐preferred language compared to those who did not, as well as between non‐CALD and CALD groups. This is the first study to assess these differences in Australia.